An FDTD interaction scheme of a high-intensity nanosecond-pulsed electric-field system for in vitro cell apoptosis applications - Phumin Kirawanich (2018)
A finite-difference time-domain analysis of a high-intensity nanosecond-pulsed electric-field (nsPEF) system, composed of a pulse-forming line (PFL) and a universal electroporation cuvette, is described. The simulation scheme is based on interactions of 1-D transmission-line equations for the PFL and 3-D Maxwell's curl equations for the cuvette volume. Simulations incorporate system adjustment to facilitate maximum transfer of electrical energy from the PFL to the cuvette medium. Experimental validation of the voltage across the cuvette electrodes through the laboratory-constructed nsPEF system with an energy density of ∼1 J/cm3reveals an overall agreement with some discrepancies. The distribution profiles of the transient field inside the cell suspension area during the excitation of 5-kV 10-ns pulses would adequately account for the feasibility of using an integrated model as a design benchmark for the interaction physics of the generated nanosecond pulses and culture vessel. The observed nsPEF effects on cells include increased transmembrane potentials across organelle membranes without permanently damaging the cell membrane, increasing the probability of electric field interactions with intracellular structures. © 2010 IEEE.